A systematic review of parenting interventions used by social workers to support vulnerable children. (July 2022) - Vseteckova, Jitka; Boyle, Sally; Higgins, Martyn
This paper reports on the findings from a systematic review of parenting interventions used by social workers to support vulnerable children in the United Kingdom. The study focused on children from birth to 11 years and 11 months based on Munro's rationale for early intervention. From the 423 papers initially identified, twelve met the inclusion criteria for this review. Four common themes were identified: developing relationships, the effectiveness of parenting interventions, societal impact on families and health and psychological concerns. The importance of effective relationships between parents and social workers was identified as key to effective parental interventions but there was limited evidence of improved outcomes for children despite this. A common factor in the studies was the level of parental deprivation which in many cases was associated with a range of mental health issues frequently seen in association with drug and alcohol abuse and domestic violence. The review identified a number of successful outcomes across a range of parenting interventions. However, what was surprising was the limited input from the children themselves within this review. Applying our findings to practice, the authors recommend a number of ways to contribute to the development of parenting interventions.